Evaluation of performance of health systems: a model for analysis - Viacava, Francisco; Ugá, Maria Alicia Domínguez; Porto, Silvia; Laguardia, Josué; Moreira, Rodrigo da Silva (Ciência & saude coletiva, 2012)
This paper presents a review of the Dimension Matrix for Evaluation of the Brazilian Health System that was initially developed in 2003, as well as a conceptual update of some of the sub-dimensions for the evaluation of health service performance, namely effectiveness, access, efficiency and appropriateness of health care. It also describes the indicator selection process as well as the results obtained in each performance dimension. The behavior of the indicators used to assess the performance of health services in Brazil, with respect to each sub-dimension, was not uniform. Areas of marked improvement were found in indicators that are influenced by activities in the field of primary care. The most significant improvements were seen in the sub-dimensions of Effectiveness and Access. With respect to the Efficiency of health services, situations of high efficiency coexist with others with substandard performance. The performance of health services in the sub-dimension of Appropriateness of Health Care was the lowest of all indicators.